Financing Secondary Education in Kenya: Cost Reduction and Financing Options Financiación de la Educación Secundaria en Kenia: Reducción del coste y opciones de financiamiento - Moses W. Ngware; Eldah N. Onsomu; David I. Muthaka (Arizona State University, 2007)
The paper examines the financing status of secondary education in Kenya and explores possible cost reduction and financing options in the long term. Educational needs for secondary education in Kenya are on the increase since the introduction of Free Primary Education in 2003. Financing of secondary education continues to be a challenge to the government, parents and communities at large. Identifying sustainable financing options that maximize on cost-effectiveness in resource utilization is therefore critical. The study utilized secondary data obtained from education trend statistics, the 2003 Kenya school census, and the Teachers Service Commission. The education simulation and financial projection tool provided the basis for projecting both growth in secondary enrollments, resource needs, and financial implications of various policy options. Some of the insights from the study show that expenditure on secondary education as a proportion of GDP and the total education public budget averaged 1.6% and 22%, respectively. Public financing is predominantly recurrent, while non-recurrent expenditures are estimated at 6%. High-income quintiles benefit more from public provision and financing of secondary education compared to the low-income quintiles. Feasible financing options would therefore include increasing secondary education revenue and fiscal allocation on non-salary expenditures. Cost reduction measures should target the expansion of quality day schools, efficiency utilization of teachers, and streamlined procurements. The paper provides research findings and makes objective projections with a view to informing researchers, education managers and policy makers. Este ensayo examina el estado de financiación de la educación secundaria en Kenia y explora posibles soluciones para la reducción del coste y opciones de financiamiento a largo plazo. Las necesidades educativas de la educación secundaria en Kenia han aumentado desde la introducción de la Educación Primaria Gratuita en 2003. La financiación de la educación secundaria sigue siendo un reto para el gobierno, los padres de familia y la comunidad en general. La identificación de opciones financieras sostenibles que utilicen al máximo la relación coste- rendimiento es, por lo tanto, un aspecto crítico. Los datos utilizados para este estudio fueron tomados de estadísticas sobre tendencias educativas, del censo escolar de Kenya 2003 y de la Teachers Service Comission. La herramienta utilizada para la simulación de la educación y la proyección financiera proporcionó la base para poder proyectar el crecimiento en matrícula en la escuela secundaria, las necesidades en cuanto a recursos y las implicaciones financieras de varias opciones de políticas educativas. Algunos hallazgos que se desprenden del estudio muestran que el gasto de la escuela secundaria como una proporción del Producto Doméstico Bruto y el total del presupuesto para la educación pública promedió 1.6% y 22%, respectivamente. La financiación pública es predominantemente recurrente, mientras que los gastos no recurrentes se calcula son un 6%. Los quintilos de ingresos altos son más beneficiados por la provision pública y el financiamiento de la educación secundaria que los quintilos de bajos ingresos. Por lo tanto, algunas opciones financieras viables incluirían el aumento a los ingresos para la educación secundaria y una asignación fiscal sobre los gastos no salariales. Las medidas de reducción de coste deberán fijar como objetivo la expansión de escuelas de calidad, eficiencia en la utilización del profesorado y una obtención de provisiones racionalizada. El ensayo informa sobre los resultados de la investigación y proporciona proyecciones objetivas con la vista puesta en informar a investigadores, gerentes educativos y hacedores de política.